Analysis of the Honesty Character Education of Class II Students During the Covid-19 Pandemic in Elementary Schools: Analisis Pendidikan Karakter Kejujuran Siswa Kelas II Pada Masa Pandemi Covid-19 di Sekolah Dasar - Livia Widya Lestari; Feri Tirtoni (Academia Open, 2021)
This research is motivated by the application of honesty character education during the Covid-19 pandemic. Schools are educational institutions that support expertise in the form of knowledge and character values. With character education, especially on honesty in elementary schools, it will create a generation of quality and good character. This thesis aims to determine the application of honesty character education in elementary schools during the Covid-19 pandemic. This study uses a descriptive qualitative approach with case study research methods with data collection techniques in the form of interviews and documentation. The results of this study indicate that teachers have implemented honesty character education for the IISDN Banjarwungu 02 class during the Covid-19 Pandemic. This research is motivated by the application of honesty character education during the Covid-19 pandemic. Schools are educational institutions that support expertise in the form of knowledge and character values. With character education, especially on honesty in elementary schools, it will create a generation of quality and good character. This thesis aims to determine the application of honesty character education in elementary schools during the Covid-19 pandemic. This study uses a descriptive qualitative approach with case study research methods with data collection techniques in the form of interviews and documentation. The results of this study indicate that teachers have implemented honesty character education for class IISDN Banjarwungu 02 during the Covid-19 Pandemic.